Empowering household economies: women’s economic contributions through the batik puspa nyidro home industry - Widiyawati, Dhea Ayu; Kisworo, Bagus (Pusat Studi Gender dan Anak, 2025)
This study examines the role of women in supporting household economic sustainability, as well as the enabling and constraining factors, through their involvement at the Puspa Nyidro Batik Home Industry in Magelang Regency, Central Java Province. Employing a qualitative research approach, the study involved five female batik workers and one manager as research participants. Data were collected through observations, in-depth interviews, and document analysis. The findings indicate that women perform three interconnected roles. First, the productive role is reflected in their participation in batik production, which contributes directly to household income. Second, the reproductive role is evident in their continued responsibility for domestic tasks, including childcare, spousal care, cooking, and household maintenance. Third, the social role is demonstrated through their active participation in community organizations, particularly the Family Welfare Movement (PKK). Despite their significant contributions, women face economic challenges, primarily low and unstable income due to fluctuating market demand. However, flexible working hours, prior batik-making skills, and strong family support serve as key driving factors that enable their sustained participation. This study contributes to the discourse on women’s economic roles in home-based industries by highlighting the intersection of productive, reproductive, and social responsibilities. It also underscores the importance of skills development and targeted economic support to strengthen the resilience of female workers in the informal sector.